2013
DOI: 10.1590/s1413-80502013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Antecipação e surpresa monetária e seus efeitos nas taxas de juros de mercado

Abstract: O objetivo deste artigo é avaliar os efeitos das ações do Comitê de Política Monetária (COPOM) sobre a curva de juros da economia brasileira, em um ambiente onde o mercado se preocupa em compreender o comportamento da autoridade monetária através de uma regra do tipo Taylor. Os resultados sugerem que o mercado tem sido capaz de antecipar adequadamente as mudanças na meta taxa Selic e que surpresas monetárias tem levado o mercado a rever seus contratos de juros DI-futuros, influenciando, assim, as taxas de juro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Thus, it is concluded that the market for higher education stocks was efficient in its semi-strong form for the event of issuance of debt securities, supporting the efficient market hypothesis that investors incorporate all available information into the pricing of the asset, with there being no abnormal gains derived from the release of resources for Fies. Comparing the results with other studies carried out within the scope of monetary policy, the results converge with those of Eid (2011) andZabot, Caetano, andCaldeira (2013), who did not find evidence of abnormalities in the stock returns before Monetary Policy Committee (Copom) announcements of an alteration in the interest rate.…”
Section: Events Studysupporting
confidence: 81%
“…Thus, it is concluded that the market for higher education stocks was efficient in its semi-strong form for the event of issuance of debt securities, supporting the efficient market hypothesis that investors incorporate all available information into the pricing of the asset, with there being no abnormal gains derived from the release of resources for Fies. Comparing the results with other studies carried out within the scope of monetary policy, the results converge with those of Eid (2011) andZabot, Caetano, andCaldeira (2013), who did not find evidence of abnormalities in the stock returns before Monetary Policy Committee (Copom) announcements of an alteration in the interest rate.…”
Section: Events Studysupporting
confidence: 81%
“…For additional details related to Focus Report, see: Focus -Relatório de Mercado (BCB, 2018a). Moreover, this relation was shown by Zabot et al (2013), from a mainstream perspective, and by Mendonça (2018), from a heterodox view.…”
Section: The Keynesian Viewmentioning
confidence: 91%
“…They find that the first measure affects the term structure for the period 2002-2009 for maturities of up to two years ahead, while the second measure is not significant. Zabot et al (2013) assume that interest rates expectations follow a Taylor rule. They then study the effect of anticipated and non anticipated components of changes in the Selic target on market rates with maturities ranging from 3 months to 3 years.…”
Section: Literature Reviewmentioning
confidence: 99%